Aeolian Geomorphology of Ergs and Dunefields in Iran. - Mehran Maghsoodi; Hamid Ganjaeian (Desert)
Iran's geographical location causes the majority of the country to be semi-arid, arid, or hyper-arid. The existence of ergs and dunefields in the central and eastern parts of Iran has caused residential areas and all kinds of land use to be affected by sand movement and dust risk. Despite this, there is no comprehensive research on ergs and dunefields in Iran. The aim of this study is to identify, classify, and monitor Iran's ergs and sand dunes, as well as their wind characteristics. We used 66 synoptic stations throughout the country, satellite images from the Ergs region (Landsat 8 and Google Earth), geological and topographical maps at scales of 1:100000, 1:250000, and 1:50000, a digital elevation model with 12.5 meter resolution, and data from field work to achieve our objectives. In addition, using different software, classification of sand dunes, wind erosion potential, and descriptive and analytic maps were prepared. According to the findings, the total area of ergs and dunefields in Iran covered approximately 2.9 percent of the country. Sand dunes come in a variety of shapes and sizes, due to climate and geomorphological diversity in different parts of Iran. Also sand dunes in the south-east of Iran have migrated at a rate of more than 18 meters per year over the last 16 years. The results of the correlation between sand dunes movement and wind characteristics show a close direct correlation, so that sand dunes have the most displacement in areas with high wind velocity and Total Drift Potential (DPt), but have low displacement in other areas due to sand dunes stabilization with vegetation and topographic obstacle.